2016
DOI: 10.1177/2045125316672135
|View full text |Cite
|
Sign up to set email alerts
|

Dosing patterns and medication adherence in bipolar disorder patients treated with lurasidone: a US retrospective claims database analysis

Abstract: Background: The aim of this study was to describe dosing patterns and medication adherence among bipolar patients who initiated lurasidone in a real-world setting. Methods: Adult bipolar patients who initiated lurasidone between 1 November 2010 and 31 December 2012 (index period) with 6-month pre-and post-index continuous enrollment were identified from the IMS RWD Adjudicated Claims US database. Patients were grouped by starting lurasidone daily dose: 20 mg (7.1%), 40 mg (62.2%), 60-80 mg (28.7%), and 120-160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In this regard, it is also worth noticing that the upcoming clinical trials should ideally investigate the impact of current and/or lifetime mixed features as primary outcomes. Similarly, greater attention and stratification of the reported results by upcoming RCTs should focus on psychotic features and (emerging) suicidality, which would on turn demand for extended longitudinal follow-up, including flexible-dose regimen arms, to better investigate medication adherence to lurasidone across varying dosing patterns [ 91 ]. This is particularly true considering that BD and mood disorders in general should be better evaluated from an extended longitudinal perspective, as originally postulated by Emil Kraepelin for “manic-depressive illness” [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is also worth noticing that the upcoming clinical trials should ideally investigate the impact of current and/or lifetime mixed features as primary outcomes. Similarly, greater attention and stratification of the reported results by upcoming RCTs should focus on psychotic features and (emerging) suicidality, which would on turn demand for extended longitudinal follow-up, including flexible-dose regimen arms, to better investigate medication adherence to lurasidone across varying dosing patterns [ 91 ]. This is particularly true considering that BD and mood disorders in general should be better evaluated from an extended longitudinal perspective, as originally postulated by Emil Kraepelin for “manic-depressive illness” [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they did not have continuous Medicaid eligibility during the 6‐month period prior to the index MDD diagnosis and the 4‐month period since the treatment initiation (index treatment); if they received any MDD treatment during the 6‐month period prior to the index MDD diagnosis (Burger et al, ; Chen et al, ; Sajatovic et al, ); if they ever received a bipolar disorder diagnosis (ICD‐9‐CM: 296.0, 296.1, 296.4–296.8, 301.11); or if patients’ index diagnosis was given by a provider with missing or unknown specialty. Moreover, MDD cases identified by providers other than PCPs, psychiatrists, or social workers/psychologists (e.g., dermatologist and neurologist), or those identified in a hospital or emergency room were also excluded in order to focus the analysis on providers who were routinely providing mental health services to children.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the efficacy of high-dose risperidone was not observed in early nonresponders to 6 mg/day, the upper limit of the ordinary dose. 22 Sajatovic and colleagues 26 reported that a real-world analysis of 1114 bipolar patients indicated that 40 or 80 mg/day were the most common starting doses of lurasidone and 55.2 mg/day was the mean maintenance dose, and that higher doses of lurasidone were prescribed to patients with comorbidities or prior antipsychotic use. Thus, an increase in a dosage within the ordinary range may be necessary unless efficacy is not shown, but trying high doses above the ordinary range is not recommended before switching from an antipsychotic to another one.…”
Section: Dosing Strategiesmentioning
confidence: 99%